2006
DOI: 10.1002/jbm.a.30950
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zoledronic acid incorporated in a poly(D,L‐lactide) implant coating on osteoblasts in vitro

Abstract: Bisphosphonates such as zoledronic acid (ZOL) are used in diseases associated with osteoclast-mediated bone loss. However, their antiresorptive activity is partly due to their effect on osteoblasts. Local application might increase the therapeutical fence and their local efficiency and reduce systemic side effects. Aim of the study was to investigate the effect of ZOL on human osteoblasts like cells in vitro with special focus on the synthesis of factors mediating osteoclast differentiation (RANKL, OPG). ZOL w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 36 publications
2
40
1
Order By: Relevance
“…This finding supports the theory that Zoledronate can have a direct anabolic effect on bone formation. Published in vitro studies are not conclusive as they demonstrate that Zoledronate can have positive as well as negative results on osteoblasts, depending on the dose and study design [11,12,56]. Orriss et al showed that the Zoledronate dose has to be increased 10-to 100-fold to achieve the same inhibitory effect on osteoblasts when those are cultured on dentin slides, a finding that supports the theory that absorbed BPs are significantly less effective on osteoblasts [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports the theory that Zoledronate can have a direct anabolic effect on bone formation. Published in vitro studies are not conclusive as they demonstrate that Zoledronate can have positive as well as negative results on osteoblasts, depending on the dose and study design [11,12,56]. Orriss et al showed that the Zoledronate dose has to be increased 10-to 100-fold to achieve the same inhibitory effect on osteoblasts when those are cultured on dentin slides, a finding that supports the theory that absorbed BPs are significantly less effective on osteoblasts [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, effects of BPs on cells of the osteoblast lineage have also been described, which raises the question if BPs can also enhance bone formation activity [6,7]. In vitro experiments have shown that low concentrations of BPs can protect osteoblasts and osteocytes against apoptosis [8,9], stimulate mineralized bone nodule formation [10], and have a beneficial effect on osteoblast differentiation and protein synthesis [11]. Specifically for Zoledronate, the most potent bisphosphonate used in clinics today, an improved mineralization and proliferation of human osteoblast-like cells has been demonstrated [12].…”
Section: Introductionmentioning
confidence: 99%
“…They also induce the intracellular production of Apppi [triphosphoric acid 1-adenosin-5-yl ester 3-(3-methylbut-3-enyl) ester], an ATP analogue (38) that induces cell apoptosis. However, the effects of bisphosphonate on osteoblast are not completely elucidated, and data from literature are controversial (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Poly-D,L-lactic-acid (PDLLA) is a common and inexpensive polymer that has been used as an implant coating material for growth factor delivery (Schmidmaier et al, 2001;Schmidmaier et al, 2004), and for BMP delivery in bone tissue engineering and defect repair (Zegzula et al, 1997;Saito et al, 1999;Saito et al, 2001a;Saito et al, 2001b;Kato et al, 2006a;Kato et al, 2006b;Yu et al, 2010). PDLLA also has the capacity to act as a local delivery system for bisphosphonates (Choi et al, 2007;Greiner et al, 2007a;Greiner et al, 2007b;Greiner et al, 2008). A local approach could overcome some of the adverse side-effects associated with systemic bisphosphonate dosing including stomach ulceration, low bioavailability of oral drugs and flu-like symptoms (Thiébaud et al, 1997;Mönkkönen et al, 1998).…”
Section: In Vivo Local Co-delivery Of Recombinant Human Bone Morphogementioning
confidence: 99%